The Ability Of Klebsiella Pneumonia And Klebsiella Oxytoca To Degrade Oil Waste - Muna Ali Hussein; Yousif Nazzal Hosee; Ayad Ismael Kadhim; Umer Jameel Ibrahim (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Crude oil contamination is one of the major environmental problems, it generated processing water pollution by hydrocarbon. Microorganisms have been used to remove or reduce the effects of environmental pollutants as bioremediation agents and the fact it is environmentally friendly. This study isolated two Klebsiella strains, Klebsiella pneumonia and Klebsiella oxytoca from wastewater of the North refineries company in Baiji according to the morphological and biochemical characteristics.This work aimed to evaluated the capacity of two Klebsiella strains to degrade the petroleum hydrocarbons efficacy, which excreted from wastewater of the North refineries company. The results showed that the Klebsiella oxytoca exhibited a higher hydrocarbon degradation capacity of 67.75% compared to Klebsiella pneumonia, which recorded 45.81%. While mixed culture (Klebsiella oxytoca and Klebsiella pneumonia) was recorded a biodegradation rate of 63.35%. The results showed that efficacy of Klebsiella oxytoca as biodegradation for oil wastewater was 30% higher than other strain.